Learning the good life : wisdom from the great hearts and minds that came before - Wilson, Jessica Hooten; Stratman, Jacob (Grand Rapids : : Zondervan, 2022)
"What is "the Good Life"? How can we live well and fully in the world? Learning the Good Life seeks to help readers answer these age-old questions through introducing them to timeless texts from some of history's wisest hearts and minds. In doing so it offers a broader, richer, and more cohesive narrative in which Christians may participate"--
Description based on print version record and CIP data provided by publisher
Keywords: Wisdom in literature; Wisdom -- History; Christians -- Books and reading